When deviance becomes sin - Senekal, Anton (Koers, 1999)
In this article a brief exposition is given o f what sin and deviance entail. This perspective is approached in terms of what is called the logovision premise. This premise essentially maintains that human perception of reality is primarily mediated through words and that only God's words allow us to see reality as it truly is. Thus we are enabled to respond appropriately to reality - especially evaluative reality. By then applying God’s words to the issues involved in the study of deviance, more clarity is hopefully achieved. This is done by discussing the respective characteristics of sin and deviance and by briefly exploring the relationship between these two phenomena. Finally some of the implications for the study o f social deviance are discussed.